2002
DOI: 10.1021/ja0264798
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor Scaffolds as New Allele Specific Kinase Substrates

Abstract: The elucidation of protein kinase signaling networks is challenging due to the large size of the protein kinase superfamily (>500 human kinases). Here we describe a new class of orthogonal triphosphate substrate analogues for the direct labeling of analogue-specific kinase protein targets. These analogues were constructed as derivatives of the Src family kinase inhibitor PP1 and were designed based on the crystal structures of PP1 bound to HCK and N(6)-(benzyl)-ADP bound to c-Src (T338G). 3-Benzylpyrazolopyrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 39 publications
6
50
2
Order By: Relevance
“…1B). This is consistent with previous observations where a similar reduction in catalytic activity was reported for analog-sensitive mutants of v-Src (21). We therefore sought to improve the catalytic activity of RapR-Src-as2 by modifying our approach for kinase activation.…”
Section: Engineering Src Kinase With Independent Activation and Inactsupporting
confidence: 89%
“…1B). This is consistent with previous observations where a similar reduction in catalytic activity was reported for analog-sensitive mutants of v-Src (21). We therefore sought to improve the catalytic activity of RapR-Src-as2 by modifying our approach for kinase activation.…”
Section: Engineering Src Kinase With Independent Activation and Inactsupporting
confidence: 89%
“…[17,28] In contrast, many serine/threonine kinases already have a bulky hydrophobic amino acid at this position (F80 in cdk2). Our enzymatic analysis, in agreement with previous studies, [16] does not indicate any substantial decline in enzymatic activity of cdk2 upon substitution of the gatekeeper residue with an amino acid lacking a side chain. The interaction with a cyclin assists in holding the cdk in an active conformation and this may be a factor in the retention of activity with F80G cdk2.…”
Section: Discussionsupporting
confidence: 93%
“…[15] With respect to serine/threonine kinases, there is limited kinetic data already published with N 6 -modified ATP analogues. [16] In addition, recent work has demonstrated that substitution at the gatekeeper residue can have profound effects on kinase catalytic efficiency. [17] In order to clarify these issues Chemical genetic studies with enlarged ATP binding sites and unnatural ATP analogues have been applied to protein kinases for characterisation and substrate identification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…N 6 -benzyl-[␥-32 P]ATP was prepared enzymatically from N 6 -benzyl-ADP by using a modified version of the protocol described in ref. 19. Two hundred microliters of a 1:1 slurry of Co 2ϩ -charged iminodiacetic acid-Sepharose beads in Hepes-buffered saline (HBS) (50 mM Hepes, pH 7.4͞150 mM NaCl) were added to an empty 2-ml BioSpin column (Bio-Rad) and washed twice with 1 ml of HBS.…”
Section: Methodsmentioning
confidence: 99%